Direct Position Estimation (DPE): A Potential Application in Geodetic Networks - Mudita, Imam (Universitas Gadjah Mada, 2024)
Direct Position Estimation (DPE) is a relatively new technique in the Global Navigation Satellite System (GNSS) that is used to estimate the user’s position, velocity, and time directly from the correlation values of the received GNSS signal with the internal replica signals of the receiver. Unlike the conventional two-step approach, DPE infers the position directly from the sampled data without intermediate steps by joining signal tracking, and the navigation technique directly compares the expected signal reception of multiple potential navigation candidates against the actual received signal. The theoretical results indicate that DPE-based GNSS receivers can achieve more robust localization than conventional two-step receivers. DPE localization algorithms that compute the navigation solution directly in the navigation domain have been proposed, providing ways to address the challenges of conventional two-step receivers at the expense of additional computational load. Despite its high computational load, DPE is a more robust positioning algorithm than conventional two-step receivers in terms of multipath mitigation. The resilience of DPE against multipath and non-line-of-sight can even potentially offer applications in geodetic networks, where robust estimators are traditionally employed to counteract outliers.